Tinjauan Pendokumentasian Yang Baik Pada Rekam Medis Pasien Rawat Inap Di Rumah Sakit Kanker Dharmais Jakarta - Bayu Fajar Ilhami; Lily Widjaja; Deasy Rosmala Dewi; Laela Indawati (Yayasan Literasi Sains Indonesia, 2022)
The contents of the Medical Record are not only data on the treatment of sick patients, but also overall health data so that it is more accurately called Health Records. In general, the Health Record is an overview of the patient's health provided by the service provider/doctor to the patient to become the patient's health record. The purpose of this study was to determine the quality of good documentation in inpatients at Dharmais Cancer Hospital. The research design is cross sectional, namely research conducted at a certain time. Data sources: article searches conducted on Google Scholar to use articles that are in accordance with the research.research method Descriptiveis to describe directly the object under study using a quantitative approach. The results of the study obtained the number of completeness of medical records reached 89.13%. The sample obtained 92 medical record files, with the results of the Initial Medical Assessment Form getting a completeness score of 88.77%, CPPT Form 87.68%, Shift Handover 90.58%, and Consultation Sheets 89.49%. Medical Record Documentation still needs to be improved. Dharmais Cancer Hospital, the number of completeness of medical records needs to be increased so that the documentation of medical records is of higher quality.